2015
DOI: 10.1145/2829988.2790035
|View full text |Cite
|
Sign up to set email alerts
|

A High-Radix, Low-Latency Optical Switch for Data Centers

Abstract: We demonstrate an optical switch design that can scale up to a thousand ports with high per-port bandwidth (25 Gbps+) and low switching latency (40 ns). Our design uses a broadcast and select architecture, based on a passive star coupler and fast tunable transceivers. In addition we employ time division multiplexing to achieve very low switching latency. Our demo shows the feasibility of the switch data plane using a small testbed, comprising two transmitters and a receiver, connected through a star coupler.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…The scalability of data center optical switches is limited by the complexity of the control plane. The optical switch architecture demonstrated in [9] scales to over 1000 ports on the data plane but requires a scheduler performing dynamic wavelength assignment that is also scalable to 1000 ports and also achieves high throughput consistent with packet timescales. In this work, we presented a parallel hardware scheduler to meet these requirements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The scalability of data center optical switches is limited by the complexity of the control plane. The optical switch architecture demonstrated in [9] scales to over 1000 ports on the data plane but requires a scheduler performing dynamic wavelength assignment that is also scalable to 1000 ports and also achieves high throughput consistent with packet timescales. In this work, we presented a parallel hardware scheduler to meet these requirements.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, TDM is used on the data plane to reduce the overall switch latency by allowing many more transmitters to access the network in a given epoch than if the switch was routed by wavelength alone. Our previous experimental demonstration showed that up to M = 25 transmitters can share a wavelength in a given epoch [9]. In this switch prototype, there are L=100 timeslots, so each timeslot is 20 ns long, which at 100 Gb/s, corresponds to 250 bytes.…”
Section: A Optical Packet Switch: Data Planementioning
confidence: 99%
See 2 more Smart Citations
“…WDM) and synchronised timeslots (i.e. TDM) to establish communication [2]. Nevertheless, reconfiguring the switch requires a fast and scalable controller.…”
Section: Introductionmentioning
confidence: 99%